Epitope(s) involving amino acids of the fusion loop of Japanese encephalitis virus envelope protein is(are) important to elicit protective immunity - Fan, Yi-Chin; Chen, Jo-Mei; Chen, Yi-Ying; Ke, Yuan-Dun; Chang, Gwong-Jen J.; Chiou, Shyan-Song (Journal of virology, 2024)
Introduction of mutations into the fusion loop is one potential strategy for generating safe dengue and Zika vaccines by reducing the risk of severe dengue following subsequent infections, and for constructing live-attenuated vaccine candidates against newly emerging Japanese encephalitis virus (JEV) or Japanese encephalitis (JE) serocomplex virus. The monoclonal antibody studies indicated the fusion loop of JE serocomplex viruses primarily comprised non-neutralizing epitopes. However, the present study demonstrates that the JEV fusion loop plays a critical role in eliciting protective immunity in mice. Modifications to the fusion loop of JE serocomplex viruses might negatively affect vaccine efficacy compared to dengue and zika serocomplex viruses. Further studies are required to assess the impact of mutant fusion loop encoded by commonly used JEV vaccine strains on vaccine efficacy or safety after subsequent dengue virus infection.